Psychological Trait Resilience Within Ecological Systems Theory: The Resilient Systems Scales. Issue 1 (2nd January 2019) - Maltby, John; Day, Liz; Flowe, Heather D.; Vostanis, Panos; Chivers, Sally
ABSTRACT: This project describes the development of the Resilient Systems Scales, created to address conceptual and methodological ambiguities in assessing the ecological systems model of resilience. Across a number of samples (total N = 986), our findings suggest that the Resilient Systems Scales show equivalence to a previously reported assessment (Maltby, Day, & Hall, 2015 ) in demonstrating the same factor structure, adequate intercorrelation between the 2 measures of resilience, and equivalent associations with personality and well-being. The findings also suggest that the Resilient Systems Scales demonstrate adequate test–retest reliability, compare well with other extant measures of resilience in predicting well-being, and map, to varying degrees, onto positive expression of several cognitive, social, and emotional traits. The findings suggest that the new measure can be used alongside existing measures of resilience, or singly, to assess positive life outcomes within psychology research.